2015
DOI: 10.1139/cjes-2014-0131
|View full text |Cite
|
Sign up to set email alerts
|

Slipstream: an early Holocene slump and turbidite record from the frontal ridge of the Cascadia accretionary wedge off western Canada and paleoseismic implications

Abstract: Slipstream Slump, a well-preserved 3 km wide sedimentary failure from the frontal ridge of the Cascadia accretionary wedge 85 km off Vancouver Island, Canada, was sampled during Canadian Coast Guard Ship (CCGS) John P. Tully cruise 2008007PGC along a transect of five piston cores. Shipboard sediment analysis and physical property logging revealed 12 turbidites interbedded with thick hemipelagic sediments overlying the slumped glacial diamict. Despite the different sedimentary setting, atop the abyssal plain fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Data from the 2008 expedition (Haacke et al, 2008) and analysis and age-dating of sediments (Hamilton et al, 2015) have revealed that the slope-failures are all likely older than ~8,000 years. Sediment cores were taken at failures C, D, and E, as well as F during a subsequent expedition (Riedel and Conway, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Data from the 2008 expedition (Haacke et al, 2008) and analysis and age-dating of sediments (Hamilton et al, 2015) have revealed that the slope-failures are all likely older than ~8,000 years. Sediment cores were taken at failures C, D, and E, as well as F during a subsequent expedition (Riedel and Conway, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sediment cores were taken at failures C, D, and E, as well as F during a subsequent expedition (Riedel and Conway, 2015). Modern sediments draping the original failure-mass include turbidites from more recent megathrust earthquakes (Hamilton et al, 2015) but sediment thicknesses were insufficient to drape the original structures. Therefore, the apparent "fresh" look from the multibeam data is misleading.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations